Dietary Electrolyte Requirement of Broiler Chicks as Affected by Dietary Protein Content - Adekunmisi, A.A.; Robbins, K.R. (Pakistan Journal of Nutrition, 2009)
A soy protein based semi-purified diet was used to estimate the optimum electrolyte balance (meq Na+, K+, Cl-/kg diet) at 3 levels of dietary crude protein. Results indicated that in diets containing 14.3% Crude Protein (CP), the optimum electrolyte balance was approximately 250 meq/kg; at 21.4% CP the optimum was about 325 meq/kg and at 28.6% CP it was about 400 meq/kg. A conventional 21% CP corn-soy broiler diet which, by calculation, contained 228 meq Na+, K+, Cl-/kg was used in two subsequent experiments. In both experiments, it was found that feed intake, gain and feed efficiency were significantly improved (p<0.05) by the addition of 100 meq Na+, K+/kg diet in diets containing 56.4 meq Cl/kg, thus, confirming an optimum electrolyte balance of about 325 meq/kg in diets containing 21% CP. It was concluded that the optimum dietary electrolyte balance of broiler chicks is dependent on diet crude protein content. Further, within the range of 14-28% CP, the optimum electrolyte balance is increased by about 11 meq/kg per 1 percentage unit increase in diet crude protein content.